Teachers’ Perceptions and Experiences of Irish Secondary School Students with OCD - Sorcha Malone; Joanne McVeigh (Education Sciences)
OCD is a prevalent mental disorder, particularly amongst adolescents, with prevalence rates between 1 and 3 percent globally. This study aimed to explore teachers’ perceptions and experiences of Irish secondary school students with OCD. Interviews were conducted with 15 secondary school (middle school/high school) teachers (4 male, 11 female). The data were analysed using Constant Comparison Analysis. In total, 35 categories emerged from which 10 domains were identified: manifestations of OCD; portrayal of OCD in the media; comorbidity; prevalence and impact; OCD in the classroom; teacher training; role as teachers; perceived ability to identify and support; barriers to identification and support; and importance of awareness and education. Further research on teachers’ understanding of OCD is recommended to inform the design of teacher training programmes to support students affected by OCD.